ANALISIS PENGENDALIAN KUALITAS PRODUK DEFLECTOR AXEL COUNTER MENGGUNAKAN METODE STATISTICAL PROCESS CONTROL DI PT. SMART TEKNIK UTAMA - Noneng Nurhayani, Noneng Nurhayani; Rahmi Rismayani Deri, Rahmi Rismayani Deri; Siti Sofiah Khoerunnisa, Siti Sofiah Khoerunnisa (Fakultas Teknik, 2023)
In the industrial sector, the quality of a product is a very important factor. The quality of the resulting product is determined based on the measurement or assessment of certain characteristics. PT. Smart Teknik Utama is a manufacturing company that produces railroad parts, one of which is the Deflector Axel Counter. This study was conducted to determine whether the existence of the production process of making this Axel Deflector Counter within the limits of statistical control or not, by using a statistical control tool, namely Statistical Process Control. The results of the analysis using the Xbar-R control chart for the type of variable defect & the P control chart for the type of attribute defect indicate that there are points outside the control limits, meaning that the production process is not under control or there are still deviations. Then identified using a fishbone diagram that the factors causing product defects come from the method, machine, man, material, and environment. After knowing the factors causing the disability, a proposed improvement was made using the 5W1H concept. The improvement proposals obtained include the need for more thorough inspection of the materials used, supervision and re-checking of the machines to be used, improving work methods for the better, providing skills training for operators, and providing safety & comfort to operators during the production process.